Targeting dendritic cells to accelerate T-cell activation overcomes a bottleneck in tuberculosis vaccine efficacy - Kristin L. Griffiths (Nature Portfolio, 2016)
A delay in T cell responses is postulated as a possible explanation for the limited efficacy of vaccines against tuberculosis. Here the authors demonstrate this T-cell block and remove it by activating endogenous dendritic cells or delivering activated dendritic cells to the lungs, enhancing immunity of mice toMycobacterium tuberculosis.